2000
DOI: 10.1128/mcb.20.23.8793-8802.2000
|View full text |Cite
|
Sign up to set email alerts
|

Association with Ets-1 Causes Ligand- and AF2-Independent Activation of Nuclear Receptors

Abstract: The vitamin D receptor (VDR) normally functions as a ligand-dependent transcriptional activator. Here we show that, in the presence of Ets-1, VDR stimulates the prolactin promoter in a ligand-independent manner, behaving as a constitutive activator. Mutations in the AF2 domain abolish vitamin D-dependent transactivation but do not affect constitutive activation by Ets-1. Therefore, in contrast with the actions of vitamin D, activation by Ets-1 is independent of the AF2 domain. Ets-1 also conferred a ligand-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 39 publications
6
46
0
1
Order By: Relevance
“…Expression of the TF v-ets erythroblastosis virus E26 oncogene homolog 1 (avian) (Ets1), important in osteogenesis (33,34), can be induced via retinoic acid, estrogen, and vitamin D3 signaling. Ets1 is responsible for activating expression of AP and osteopontin.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of the TF v-ets erythroblastosis virus E26 oncogene homolog 1 (avian) (Ets1), important in osteogenesis (33,34), can be induced via retinoic acid, estrogen, and vitamin D3 signaling. Ets1 is responsible for activating expression of AP and osteopontin.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand binding induces conformational changes in the VDR, which promote heterodimerization with retinoid X receptor (RXR) and recruitment of a number of nuclear receptor coactivator proteins [78]. Ligand-independent activation of VDR/RXR heterodimers activates a reporter driven by the prolactin promoter, which is in the presence of Ets-1 that induces a conformational change in the receptor, which creates an active interaction surface with coactivators even in the AF2-defective mutants [79].…”
Section: Rxr Dominates the Nuclear Import And Export Of The Unligandementioning
confidence: 99%
“…For example, although some reports indicate a central role for ERKs and protein kinase C-␣ signaling in estrogen regulation of cell cycle progression (Castoria et al, 1999;Manole et al, 2001;Marino et al, 2001), other authors have shown cell cycle effects of these hormones independently from these cascades. Furthermore, a growing body of evidence suggests the existence of cross talk between estrogen receptors and other signaling pathway effectors (Tolon et al, 2000;Coleman and Smith, 2001).…”
Section: Introductionmentioning
confidence: 99%